The public health implications of the cost-of-living crisis: Outlining mechanisms and modelling consequences - Philip Broadbent; Rachel Thomson; Daniel Kopasker; Gerry McCartney; Petra Meier; Matteo Richiardi; Martin McKee; Srinivasa Vittal Katikireddi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
The UK, and other high-income countries, are experiencing substantial increases in living costs. Several overlapping and intersecting economic crises threaten physical and mental health in the immediate and longer term. Policy responses may buffer against the worst effects (e.g. welfare support) or further undermine health (e.g. austerity). We explore fundamental causes underpinning the cost-of-living crisis, examine potential pathways by which the crisis could impact population health and use a case study to model potential impacts of one aspect of the crisis on a specific health outcome. Our modelling illustrates how policy approaches can substantially protect health and avoid exacerbating health inequalities. Targeting support at vulnerable households is likely to protect health most effectively. The current crisis is likely to be the first of many in era of political and climate uncertainty. More refined integrated economic and health modelling has the potential to inform policy integration, or 'health in all policies'.
Keywords: 330; Health; Income Dynamics; Microsimulation; Life Course Analysis; Psychology; Household Economics; Poverty; Welfare Benefits; Economics; Public Policy; Living Standards; Well Being; Economic Policy